Attitudes of psychological counselors in special needs centers towards using artificial intelligence in providing counseling services (Al-Farooq Journal of Sciences, 2026)
This exploratory study aimed to investigate the attitudes of psychological counselors in special needs centers toward utilizing artificial intelligence (AI) technologies in counseling services, and to assess their level of acceptance of these digital applications. To achieve these objectives, the study adopted an exploratory descriptive approach. A two-axis questionnaire (Attitudes and Acceptance) was developed and administered to a small, purposive sample of (10) male and female counselors working in special education centers. Data were statistically analyzed using weighted means, percentage weights, and the non-parametric Mann-Whitney U Test.The results of the first hypothesis revealed highly positive attitudes toward integrating AI, with a weighted mean of (2.62 out of 3) and a percentage weight of (87.3%). Counselors indicated that AI accelerates diagnosis and minimizes routine administrative burdens. Furthermore, the results of the second hypothesis showed no statistically significant differences in acceptance levels based on gender (male/female), with a generated p-value of (0.711), reflecting uniform digital acceptance driven by shared professional challenges. The study concluded with several recommendations, most notably the urgent need to provide specialized training programs for counselors and to secure the digital infrastructure and safety protocols to protect data confidentiality within special needs centers.
Keywords: Attitudes, Acceptance, Psychological Counselors, Special Needs, Artificial Intelligence